Pengaruh Pemberian Pupuk Kandang Ayam Terhadap Pertumbuhan dan Produksi Tanaman Semangka (Citrullus Vulgaris.) - Ardianus Wuli; Henderikus Darwin Beja; Julianus Jeksen (Jurnal Ilmiah Wahana Pendidikan, 2021)
Watermelon plant (Citrullus vulgaris), is a fruit plant that grows vines which in English is called Water Mellon. Watermelon comes from the dry tropical and subtropical regions of Africa, then grows rapidly to various countries such as: South Africa, China, Japan, and Indonesia. The aim of the researcher was to determine the effect of the dose of chicken manure on growth, and the best dose of chicken manure on the production of watermelon (Citrullus vulgaris). The method used in this study was a randomized block design (RBD) with four replications and five treatments, namely, PK0: 0 tons / ha or without fertilizer, PK1: 20 tons/ha, PPK2: 30 tons/ha, PK3: 40 tons/ha, PK4: 50 tons/ha. Based on the results of analysis of variance using a randomized block design (RBD), the results showed that the application of chicken manure had no significant effect on plant length, number of flowers, and had a significant effect on fresh fruit weight tan-1 and fresh fruit weight ha-1. The optimum dose of chicken manure 50 ton/ha is the best treatment for watermelon (Citrullus vulgaris) production. optimal production wpith an average weight of fresh fruit ha-1 reaching 350 tons